Acessibilidade digital no Brasil: avanços eregressos na inclusão social de pessoas com deficiência na cibercultura - Blankenburg, Rodrigo (2023)
This Master’s Thesis addresses the regression in the application of accessibility on the pages of the federal public domains in the face of the universal world standards set by the World Wide Web Consortium, the W3C, depriving them of access to information, communication and especially their rights in relation to the services and information, available in cyberspace, segregating the inclusion of people with disabilities, on the Web. As a result, it is possible to meet two empirical developments related to the theme: (1) The cybercultural dromological advance allows us to reach infinite possibilities of interactions in the globalized digital world, such as, among many others, the use of the services available on the federal public portals, from actions carried out in the technological devices, provided that there is cognitive knowledge capable of such handling; (2) As contradictory as it is, this same advance is controversial when we observe the aforementioned development from the perspective of social inclusion in relation to the use of cyberspace, as there is a barrier between the disability community and the technological apparatus, stemming from the lack of public investment in these portals and the social disinterest applied to Brazilian digital services, making knowledge interactions limited, rendering the services available on these public domains inaccessible and inoperative for people with disabilities. In this regard, the question arises to what extent state-owned companies are, in fact, open to welcoming the public through digital inclusion, using their channels as an example, supporting and benefiting millions of Brazilians to evolve their capacities and utilize their services in favor of their own opportunities in cyberculture. Based on these findings, uncertainties arise regarding the extent to which people with disabilities are covered by their own public constitutions and how much the Federal Public Ministry, together with the Secretariats of Persons with Disabilities, are attentive to these inspections and monitoring, in the face of an increasingly alienated society. The theoretical framework of reference is formed by contemporary authors such as Trivinho, Kumar, Virilio, Heidegger, Marx, Cohn, among others and is based on the constitutions that support people with disabilities, perspectives of dromology, post-structuralism, post-Marxism, post-industrialism and the current critique of communication and advanced media civilization, as well as research that corroborates with the based analyses